Food consumption and risk of childhood asthma. Issue 8 (12th May 2015) - Lumia, Mirka; Takkinen, Hanna‐Mari; Luukkainen, Päivi; Kaila, Minna; Lehtinen‐Jacks, Susanna; Nwaru, Bright I.; Tuokkola, Jetta; Niemelä, Onni; Haapala, Anna‐Maija; Ilonen, Jorma; Simell, Olli; Knip, Mikael; et al.
Abstract: Background: The consumption of foods rich in n‐3 polyunsaturated fatty acids has been proposed to protect against childhood asthma. This study explores the association of food consumption (including cow's milk (CM)‐free diet) in early life and the risk of atopic and non‐atopic asthma. Methods: Food intake of 182 children with asthma and 728 matched controls was measured using 3‐day food records, within the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Nutrition Study cohort. The diagnoses of food allergies came both from the written questionnaire and from the registers of the Social Insurance Institution. Conditional logistic regression with generalized estimating equations framework was used in the analyses. Results: The diagnosis of cow's milk allergy (CMA) led to multiple dietary restrictions still evident at 4 yr of age. Even after adjusting for CMA, higher consumption of CM products was inversely associated with the risk of atopic asthma and higher consumption of breast milk and oats inversely with the risk of non‐atopic asthma. Early consumption of fish was associated with a decreased risk of all asthma. Conclusions: Dietary intake in early life combined with atopy history has a clear impact on the risk of developing asthma. Our results indicate that CM restriction due to CMA significantly increases and mediates the association between food consumption and childhood asthma risk.